STRATEGY TO IMPROVE STUDENTS' LITERACY AND NUMERACY ABILITIES - Heni Kuswanti (Sean Institute, 2023)
Education is considered a key pathway to prepare a generation expected to cope with the complexity of the challenges of the 21st century. Literacy and numeracy play a central role in equipping learners with essential skills to face the complex challenges of the modern era. This study aims to provide in-depth insights into effective strategies in improving students' literacy and numeracy skills to face the demands of an increasingly complex era. The research method uses a literature review with three main steps: identification of relevant literature, literature analysis, and preparation of conclusions. The results showed two main strategies, namely integrating technology in learning and contextual learning. Technology integration includes the use of interactive applications, adaptive learning software, and online resources. Contextual learning focuses on the application of literacy and numeracy in everyday life, involving project-based methods, internships, and problem-based learning. The use of technology opens up opportunities to enrich the learning experience of students by presenting material in an interactive and relevant manner. Contextual learning, through real-life situations, allows learners to relate literacy and numeracy concepts to their practical experience. Strategy evaluation involves monitoring student progress, assessment of learning outcomes, and feedback from teachers. By implementing these strategies, learners can develop relevant literacy and numeracy skills, provide in-depth insights into the world of work through internships, field trips, and improve problem-solving skills with a problem-based approach. Through this hands-on experience, learners prepare to face real-world challenges and become productive members of society.